Contribution to the knowledge of Chinese Gryllacrididae (Orthoptera) III: New additions of Metriogryllacris Karny, 1937 - Liu, Jing; Bin, Wei; Bian, Xun (Zootaxa, 2021)
In this paper, one new species is described from Yunnan province viz. Metriogryllacris (Metriogryllacris) nigrilimbis Liu & Bian sp. nov.. Based on the specimens from Guangxi Zhuang Autonomous Region, the morphological characters of Metriogryllacris (Metriogryllacris) permodesta (Griffini, 1914) are provided. All specimens are deposited in Guangxi Normal University.